PARTISIPASI MASYARAKAT PADA PENANGGULANGAN BANJIR DALAM PERSPEKTIF PENDIDIKAN KEWARGANEGARAAN - Imamsari, Fajar Susi; Triastuti, Rini; ., Wijianto (Educitizen, 2017)
The aim of this research was to 1) know society participation in handling of floods natural disaster and 2) implication to environmental caring in handling of floods natural disaster in Sub-District of Jebres.Result of research indicate that society participation in order to handling of floods very real, especially at activity listen carefully emergency, but floods cause state's finance burden addition, especially to rehabilitate and cure function of pre medium damage public. The happening of with refer to floods during short relative and recurred per annum, claiming bigger effort anticipating it, so that loss earn minimization. Implication to environmental caring in handling of floods natural disaster in Sub-District of Jebres cover seven relied on storey its interaction mechanism, that is: (1) deduction (resistance); (2) transfer of information (information sharing); (3) consultancy (commitment no with consultation); (4) consensus and intake of agreement with (agreement and building consensus); (5) collaboration; (6) enable ness with division of risk (sharing empowerment-risk); (7) partner and enable ness (partnership and empowerment). Keywords: Participation Society, Strive Handling Floods, Civic Education of Perspective